(untitled) ("Conference on Universal Science Research 2023", 2024)
One of the hot topics of modern healthcare is acute coronary syndrome (ACS). During the work it was carried out assessment of the hospital stage of patient management, patient adherence to treatment, long-term clinical and social consequences